Physicochemical and bioactive properties of Apis and stingless bee (Meliponini) honey from Brazilian Caatinga - Araújo, Filipe Gomes de; Araújo, Nícolas Oliveira de; Oliveira, Victor Rafael Leal de; Leite, Ricardo Henrique de Lima; Santos, Francisco Klebson Gomes dos; Aroucha, Edna Maria Mendes (Acta Scientiarum. Animal Sciences, 2023)
Since the composition of honey varies with the species of bee as well as flowering and geographical aspects, this study aimed to evaluate the physicochemical and bioactive properties of Apisand stingless bees’honey from the Brazilian Caatinga. Samples of different species of Apis mellifera L.Meliponini (Melipona subnitida, Frieseomellita varia, Melipona mandacaia, Plebeia sp.) and Apis mellifera L.werecollected from honey producersin the state of Rio Grande do Norte. Honey from A. mellifera and stingless bees showed physicochemical differences in some parameters, especially in moisture, free acidity, HMF, water activity, sugars and electric conductivity. There were no differences in color between honeys from A. mellifera and stingless bees. Honeys fromPlebeia sp., F. varia and A. mellifera showed higher antioxidant capacity followed by honeys fromM. mandacaia and M. subnitida. Flavonoids had little influence on the differentiation of antioxidant activities of stingless bees, while the opposite occurred with the phenolic content, where honeys with the highest levels of phenolic also showed higher antioxidant capacity.